Hubungan Kualitas Tidur Dengan Konsentrasi Belajar Pada Siswa/I Kelas VII-IX MTS Miftah Assa’adah Di Pondok Aren Kota Tangerang Selatan - Beata Rivani; Hadi Nugroho; dyah Juliastuti; Talia Rosali (Jurnal Kesehatan STIKes IMC Bintaro, 2023)
Introduction : Concentration is an important aspect in supporting adolescents to achieve good results. Adolescents who face learning difficulties experience a decrease in concentration during learning which can be caused by sleepiness and fatigue due to lack of sleep. The purpose of research : knowing the relationship between sleep quality and learning concentration in class VII-IX MTs Miftah Assa'adah in Pondok Aren, South Tangerang City Year 2022. Research methods : Quantitative research design with Cross Sectional approach. The sample technique used by the researcher is a statified random sampling technique with a total of 66 respondents. The research instrument was a questionnaire sheet. Analysis of research data using the Chi Squere test. Results of research : based on the results of the study the most know to have poor sleep quality were 43 people (65.2%), the most had low learning concentration, namely 39 people (59.1%). Conclusion : There is a relationship between sleep quality and learning concentration in class VII-IX MTs Miftah Assa'adah in Pondok Aren, South Tangerang City Year 2022 (p-value 0,000 ; OR 13,6). Suggestion : It is hoped that community nurses can motivate adolescents to maintain their quality and sleep patterns in an effort to increase learning concentration. Nurses must also be able to explore the causes of decreased concentration in learning in addition to sleep quality factors.